2010
DOI: 10.1560/ijee.56.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Passerine Migratory Waves: Evidence from the Blackcap at a Stopover Site

Abstract: Hundreds of millions birds migrate through Israel every spring, usually in several waves during which a large number of birds are seen flying over Israel for several days, followed by periods in which only a small number are spotted. The aims of this study were to (1) determine whether the spring migration of the blackcap demonstrates a wave pattern, (2) determine the effect of weather conditions en route on the number of blackcaps arriving and forming each wave, and (3) use morphological characteristics and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
3
1
0
Order By: Relevance
“…In the blackcap, early females had shorter wings than late females. This trend is partially in agreement with a previous study on the blackcap in Israel 61 , which suggested that blackcaps (both sexes) from the early migration phase had shorter wings than the later arrivals. The same study found that the shorter wing individuals breed at a more southerly or westerly destination in Europe 61 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the blackcap, early females had shorter wings than late females. This trend is partially in agreement with a previous study on the blackcap in Israel 61 , which suggested that blackcaps (both sexes) from the early migration phase had shorter wings than the later arrivals. The same study found that the shorter wing individuals breed at a more southerly or westerly destination in Europe 61 .…”
Section: Discussionsupporting
confidence: 93%
“…This trend is partially in agreement with a previous study on the blackcap in Israel 61 , which suggested that blackcaps (both sexes) from the early migration phase had shorter wings than the later arrivals. The same study found that the shorter wing individuals breed at a more southerly or westerly destination in Europe 61 . The longer wings of the later arrivals may therefore facilitate adjustment to the fast spring vegetal growth in breeding grounds in eastern Europe compared to the western range 82 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The second factor we tested, fuel load, did not support our prediction that there would be differences in the cost of migration across the range, rather individuals from both northern and southern latitudes arrived with similar fuel loads. These results are similar to other studies [ 8 , 35 37 ] that found no relationship between fuel load and migratory distance. Moreover, most individuals in this study, as well as ruby-throats from this location previously described by Zenzal and Moore [ 15 ], typically arrived with some fuel stores.…”
Section: Discussionsupporting
confidence: 92%